Acceptability and feasibility of HIV recent infection surveillance by healthcare workers using a rapid test for recent infection at HIV testing sites - Malawi, 2019 - Melissa M. Arons; Kathryn G. Curran; Malango Msukwa; Joe Theu; Gabrielle O'Malley; Alexandra Ernst; Ireen Namakhoma; George Bello; Carson Telford; Vedapuri Shanmugam; Bharat Parekh; Evelyn Kim; et al. (BMC, 2022)
Abstract Background The Malawi Ministry of Health implemented a new surveillance activity in April 2019 to detect recent HIV infections using a rapid test for recent infection (RTRI) to identify areas of ongoing transmission and guide response activities. Setting At 23 health facilities in Blantyre District, healthcare workers (HCWs) were trained to conduct recent infection testing. In September 2019, we conducted a cross-sectional survey at these sites to explore the acceptability and feasibility of integrating this activity into routine HIV testing services (HTS). Methods Research assistants interviewed HCWs using a semi-structured survey. Descriptive statistics were used to summarize quantitative responses and thematic analysis was used to group open-ended text. Results We interviewed 119 HCWs. Eighty-two percent of participants reported the RTRI was easy-to-use. HCWs perceived high client acceptability; 100% reported clients as 'somewhat' or 'very accepting'. Challenges included 68% of HCWs estimating they spend ≥20 min beyond routine HTS per client for this activity and 51% performing at least two additional finger pricks to complete the testing algorithm. HCWs differed in their perceptions of whether results should be returned to clients. Conclusion This study assessed HCW experiences using point-of-care RTRIs for HIV recent infection surveillance. Overall, HCWs perceived RTRIs to be acceptable, easy-to-use, and valuable. Though only clients with new HIV diagnoses are tested for recent infection, additional time may be substantial at high-volume health service delivery points. Providing response plans or aggregated recent infection results to HCWs and/or clients may support motivation and sustainability of this novel surveillance activity.